การพัฒนารูปแบบองค์กรแห่งการเรียนรู้ของโรงเรียนอนุบาลประจำจังหวัด - ทองมี, ถวัลย์ (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์ 1) เพื่อพัฒนารูปแบบองค์กรแห่งการเรียนรู้ของโรงเรียนอนุบาลประจำจังหวัด 2) เพื่อตรวจสอบความสอดคล้องของรูปแบบองค์กรแห่งการเรียนรู้ของโรงเรียนอนุบาลประจำจังหวัดกับข้อมูลเชิงประจักษ์ กลุ่มตัวอย่างที่ใช้ในการวิจัยได้แก่ ผู้บริหารและครูโรงเรียนอนุบาลประจำจังหวัด จำนวน 670 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่แบบสอบถาม แบบสัมภาษณ์ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐานการวิเคราะห์องค์ประกอบเชิงยืนยัน ส่วนข้อมูลที่ได้จากการสัมภาษณ์และการสนทนากลุ่มใช้การวิเคราะห์เนื้อหา ผลการวิจัย พบว่า 1. รูปแบบองค์กรแห่งการเรียนรู้ของโรงเรียนอนุบาลประจำจังหวัด มี 10 องค์ประกอบ แบ่งเป็น 2 ด้าน คือ ด้านบุคคล ประกอบด้วย ภาวะผู้นำ การมีจิตสำนึก การมีคุณธรรม การเรียนรู้ ความคิดเชิงระบบ การมีสุขภาพดี และด้านสถานศึกษา ประกอบด้วย การมีวิสัยทัศน์ เทคโนโลยี โครงสร้างสถานศึกษา และการจัดการความรู้ 2. รูปแบบองค์กรแห่งการเรียนรู้ของโรงเรียนอนุบาลประจำจังหวัด มีความสอดคล้องกลมกลืนกับข้อมูลเชิงประจักษ์ DEVELOPMENTS OF LEARNING ORGANIZATION MODEL FOR PROVINCIAL KINDERGARTENS The objectives of this research were to : 1) develop a learning organization model of provincial kindergartens, and;2) investigate the agreement between the learning organization model of provincial kindergartens and authentic data. The samples were 660 administrations and teachers of provincial kindergartens. The research instruments were a questionnaire and an interview inventory. The statistics used for data analyses were frequency, percentage, mean, standard deviation,verifying factor analysis, and content analysis was used with the data obtained from the interview and group discussion. The results were as follows: 1. The model of the learning organization of the provincial kindergartens was composed of 10 factors; the personnel aspects included having leadership, consciousness, virtue, learning, systematic thinking, and good health; and the educational institution aspects included having vision, technology, educational institution structure, and knowledge management. 2. According to the model of the learning organization of the provincial kindergartens and the authentic data,the investigation showed the model of the learning organization of the provincial kindergartens harmoniously agreed with the authentic data.